Evaluating the Velocity and Extent of Cortical Venous Filling in Patients With Severe Middle Cerebral Artery Stenosis or Occlusion - Lin, Jia'Xing; Cheng, Zhong'Yuan; Shi, Ying'Ying; Cai, Xiang'Ran; Huang, Li'An (Frontiers in Neurology, 2021)
Objective: To investigate the velocity and extent of cortical venous filling (CVF) and its association with clinical manifestations in patients with severe stenosis or occlusion of the middle cerebral artery (MCA) using dynamic computed tomography angiography (CTA). Methods: Fifty-eight patients (36 symptomatic and 22 asymptomatic) with severe unilateral stenosis (≥70%) or occlusion of the MCA M1 segment who underwent dynamic CTA were included. Collateral status, antegrade flow, and CVF of each patient were observed using dynamic CTA. Three types of cortical veins were selected to observe the extent of CVF, and the absence of CVF (CVF-) was recorded. Based on the appearance of CVF in the superior sagittal sinus, instances of CVF, including early (CVF1), peak (CVF2), and late (CVF3) venous phases, were recorded. The differences in CVF times between the affected and contralateral hemispheres were represented as rCVFs, and CVF velocity was defined compared to the median time of each rCVF. Results: All CVF times in the affected hemisphere were longer than those in the contralateral hemisphere (p < 0.05). Patients with symptomatic MCA stenosis had more ipsilateral CVF- (p = 0.02) and more delayed CVF at rCVF2 and rCVF21 (rCVF2-rCVF1) (p = 0.03 and 0.001, respectively) compared to those with asymptomatic MCA stenosis. For symptomatic patients, fast CVF at rCVF21 was associated with poor collateral status (odds ratio [OR] 6.42, 95% confidence interval [CI] 1.37–30.05, p = 0.02), and ipsilateral CVF- in two cortical veins was associated with poor 3-month outcomes (adjusted OR 0.025, 95% CI 0.002–0.33, p = 0.005). Conclusions: Complete and fast CVF is essential for patients with symptomatic MCA stenosis or occlusion. The clinical value of additional CVF assessment should be explored in future studies to identify patients with severe MCA stenosis or occlusion at a higher risk of stroke occurrence and poor recovery.